Praseologisms of the Ukrainian Language in the Media Discourse: Cognitive Aspect (Linguostylistic Studies, 2020)
Cognitive modeling of discourse is considered to be a field of research, the aim of which is to study the structures, representing the knowledge and ways of the discourse conceptual organization in the process of its verbalization and perception.Phraseologisms as symbolic representatives of diverse knowledge in the human mind reflect the peculiarities of thinking, worldview in the process of communication. In this regard, it is important to study phraseological units that are used to transmit different intentions in both explicit and implicit forms in media discourse, from the standpoint of cognitive and pragmatic aspects.The elucidation  of the cognitive processes of perception of the reality  phenomena by means of phraseology in media discourse, as well as the analysis of pragmatic parameters of the phraseology functioning  is the purpose of this scientific research. The descriptive method, functional-pragmatic, cognitive and discourse analysis method are used in the study.Phraseologisms are the means of storing and organizing phraseological knowledge about the world around us in the human mind of society. The analyzed phraseological units in the media discourse reflect the perception of negative situations related to the socio-political sphere in the country as a whole. There is a clear evidence of the features inherent in the Ukrainian people mentality, which is manifested, in particular, in the ability to reproduce and be critical about the negative manifestations of actions and deeds of people.Phraseological units as an element of headlines, besides informative and communicative functions, have additional emotional and expressive meaning that arouses interest and attracts the readers’ attention. Transformation of phraseological units realizes their pragmatic potential, which contributes to the effective impact on the recipient. The use of phraseological units in media discourse promotes the implementation of various tactics: self-presentation, discredit of the opponent etc. The analysis of the phraseological unit usage in media discourse in the cognitive aspect allows tracing the features of the conceptual sphere of both the individual and the Ukrainian people as a whole.
Keywords: internal form; cognitive analysis; media discourse; phraseological unit (PhU)